2020
DOI: 10.3390/ijerph17155270
|View full text |Cite
|
Sign up to set email alerts
|

DANGER! Crisis Health Workers at Risk

Abstract: The occupational hazards of health workers (HWs) in standard work environments have been well defined in both the developed and developing world during routine working conditions. Less defined are the hazards to HWs during pandemics, epidemics, natural disasters, wars, conflicts, and other crises. How do crises affect the infrastructure of medical systems? What are the distinct needs of the patient population during crises? What are the peculiarities of the Crisis Health Worker (CHW)? What are the known CHWs’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…Therefore, complementary analysis methods should be used for wood dust with a larger dimensional span. Only then is it possible to detect and quantify the content of the finest dust particles and, thus, to estimate the occupational health risks accordingly [30,31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, complementary analysis methods should be used for wood dust with a larger dimensional span. Only then is it possible to detect and quantify the content of the finest dust particles and, thus, to estimate the occupational health risks accordingly [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported very similar particle size distributions between pine and oak; others reported that hardwood dust is finer than softwood dust [25]. Depending on the treatments to which wood has been subjected before machining, dust can contain preservatives, additives, or adhesives [30][31][32][33][34][35][36][37][38]. The greatest occupational risk is caused by the finest dust particles (inhalable fraction), which, when dispersed in the ambient air, can lead to serious short-term and long-term human health problems [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Esto compromete la salud mental y provoca agotamiento físico y emocional 8 . Se puede pensar que quienes laboran en condiciones de crisis son inmunes a lesiones o enfermedades, ya que su trabajo es curar enfermos y heridos, pero realmente son muy vulnerables 9 .…”
Section: Artículo De Revisiónunclassified
“…However, as frontline health workers, CHWs were extremely vulnerable to experiences of burnout, compassion fatigue, and moral distress. The U.S. Centers for Disease Control and Prevention (CDC, 2020) described the onset of COVID-19 as a “fast-moving public health crisis.” Frontline health personnel operating during public health crises are at disproportionate risk for experiencing poor mental health, including emotional distress and burnout (Deng & Naslund, 2020; Harrell et al, 2020). Burnout is characterized by emotional exhaustion, cynicism or depersonalization, and poor professional efficacy (Harrell et al, 2020; Maslach et al, 2001).…”
Section: Introductionmentioning
confidence: 99%